Analisis Iqalah pada E-Commerce dalam Erspektif Hukum Ekonomi Syariah - Adriandi Kasim (Al-'Aqdu: Journal of Islamic Economics Law, 2022)
This study aims to review or study Iqalah in E-Commerce from the perspective of Islamic Economic Law as an effort to provide a conceptual framework for Iqalah in e-commerce as well as how it relates to positive law. The methodology used in this research is qualitative, in the form of library research, using data related to the issues raised as reading material. The purpose of this article is to develop an overview of the extent to which e-commerce against iqala is permissible in Islam. In this study, the authors found important things that are interesting to be presented in this study, namely: First, e-commerce, as a digital trading platform because of its position in Sharia law, is considered to meet the right standards, so it is permissible to trade online. Second, Iqalah as a contract in the second order in buying and selling transactions, namely cancellation, cancellation is very vulnerable in e-commerce transactions, because the seller and buyer are not in the same room, so the goods being traded are not known effectively. Third, the final result of this study shows that the term Iqalah or also known as cancellation is considered halal by the scholars as well as the opinions of several Hadith, but if iqalah enters the realm of law that is not based on normative values such as the Qur'an and As-Sunnah, then this iqala will be considered a broken promise.